PERANAN KANWIL KEMENKUM NTB DALAM MENINGKATKAN PENDAFTARAN HKI OLEH UMKM DI NTB - Siti Yulianah M. Yusuf; Basuki Sri Hermanto; Iswan, Iswan (Juremi: Jurnal Riset Ekonomi, 2025)
One of the efforts to develop MSMEs is by registering IPR. IPR registration, especially brands, is very important for MSMEs because it provides legal protection for their brands and products, and increases competitiveness and brand value. This protects MSMEs from brand imitation, increases consumer trust and opens up opportunities for business development, including royalties if their brands are used by other parties. Legal protection of Intellectual Property is important in encouraging business growth and innovation in the region. Intellectual Property Rights (IPR) are very important for MSMEs because they provide legal protection for works and innovations, increase product competitiveness, and encourage economic growth. IPR also helps MSMEs to gain customer trust, facilitate access to financing, and increase business value.